Analyzing the Sustainable Development Goals (SDGs) in the Gastronomy of the Paraiba Backwoods (Research, Society and Development, 2021)
The gastronomy has grown as an attraction within the tourist experience of the visitor and an integral part of the local culture. Thus, rethinking gastronomic tourist activities in a more sustainable way, in the light of the 2030 Agenda and its 17 Sustainable Development Goals, and aligning these themes, the present study sought to analyze how artisanal goat's cheese, produced on the Farm Carnaúba from Taperoá - Paraíba, can contribute to the promotion of culture and job creation, relating it to the SDGs. As for the methodology, it is an exploratory research in relation to its objectives; with regard to technical procedures, the research includes a case study, at Fazenda Carnaúba, with the application of questionnaires to cheese consumers, as well as the producer / owner. Regarding the research question, it is considered an exploratory, bibliographic and documentary study. Being considered a qualitative research, with a quantitative bias to interconnect the objectives of the study and the respective SDGs through a graphic measurement of the responses obtained in the questionnaires, with the help of RStudio software to generate this graphic material. Dessarte, it was noticed that artisanal cheese contributes as a promoter of local culture and a generator of jobs and income; it was also identified that the product collaborates directly with the development of goals and objectives contained in the Agenda 2030 SDGs.